The Church of the Holy Sepulchre in text and archaeology - Kelley, Justin L., (Archaeopress Publishing Ltd., 2019)
This text studies the archaeological record of the Church of the Holy Sepulchre, surveying past excavations as well as recent research carried out within the church over the past three decades. An archaeological survey provides historical context for the second part of the work - a collection of primary sources pertinent to the history of the church.